The Existence of Brebes Lor Wedding Traditional Events in the Era of Globalization in the Perspective of Legal Culture - Maulida, Irma; Handiriono, Raden; Marlina, Tina; Ika Putri, Dessy; Kamil, Insan (Ann Publisher, 2024)
Indonesian culture from time to time has always undergone very rapid changes, this change occurs because of the factors of the people who really want these changes and the entry of elements of globalization into Indonesian culture. One of the cultures that is still developing in the community is the tradition of traditional marriage, such as the traditional wedding event of Brebes Lor. However, along with the development of the times and the influence of globalization, this tradition faces considerable challenges. This study aims to analyze the existence of Brebes Lor wedding customs in the era of globalization from a legal and cultural perspective, focusing on the preservation efforts carried out by the Brebes Regency Culture and Tourism Office and the obstacles faced in preserving Brebes Lor wedding customs. The research method used is a normative juridical approach, a type of qualitative research by examining literature materials (secondary data). The results of the study show that the Culture and Tourism Office of Brebes Regency has made various efforts to preserve the traditional wedding event of Brebes Lor, such as socializing the bridal makeup association in Brebes, namely the Indonesian Bridal Makeup Association (HARPI) Melati Bumiayu and collaborating with them in compiling the tradition of mapag besan. However, there are a number of obstacles in the preservation of this marriage custom, such as the lack of public interest in using Brebes clothing and makeup, as well as the inhibition of socialization to the community due to the large cost and long time. Therefore, the Tourism and Culture Office needs to make maximum use of information technology to introduce this traditional event to the wider public in order to save costs in conducting socialization, such as making videos of Brebes Lor traditional marriage events, then actively sharing them through social media.